The factors affecting knowledge sharing behaviour within a case study Taiwanese small business - Hsing, H. Lee (2016)
Organisations need to create, retrieve and distribute new knowledge within their companies before applying it to gain, or maintain competitive business.Additionally, recent research has identified a variety of factors that lead to effective knowledge sharing, such as motivation and culture. Moreover, there is few established body of literature that has identified discernible difference between China and Taiwan.Nearly all of the knowledge management literature is in respect of the cross cultural aspect of modern international business, largely in interactive networking, knowledge acquisition and sharing (Holden, 2002).However, SMEs are recognised to be a distinct industry sector with some characteristic elements of culture that will impact upon knowledge sharing with regard to the stages of creation, transfer, sharing, integration and translation into practice.Factors, including elements relating to cultural perspectives, were discussed arising from the case study of a small Taiwanese company. The research methodology was based on qualitative research and a case study. Given the objectives of the research, indepth interviews would be necessary to supplement the research.Using constructivist grounded theory this research examined how humans construct reality.It concludes that the organisational context and culture are significant factors that help employees to carry out their tasks.Additionally, the Taiwanese organisational context and how it impacts on interactions between employees and with management, was another important factor.